Nonlinear properties and stability of SnO2 varistors prepared by evaporation and decomposition of suspensions - Brankovic, G.; Brankovic, Z.; Varela, José Arana [UNESP] (Elsevier B.V., 2005)
SnO2 varistors doped with CoO, Cr2O3 and Nb2O5 were prepared by evaporation and decomposition of suspensions. The composition of the varistors was optimized to improve electrical properties, such as nonlinearity, leakage current and electrical stability. The best results were achieved with the following composition: 99.15% SnO2 +0.75% CoO+0.05% Cr2O3 +0.05% Nb2O5. Samples showed high density, reaching 99.5% of the theoretical density, as well as an homogeneous microstructure. The nonlinear coefficient was higher than 30 in the current range from 10(-7) to 10(-2) A/cm(2). The leakage current was 0.86 mu A/cm(2). These samples showed high stability of electrical parameters when they were exposed to high current of 27 mA/cm(2) for different time periods up to 30 min. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: varistor; electrical properties